The Portrayal of a Mediator : The Social Network of Peter in Luke-Acts - Dörpinghaus, Jens [Verfasser] (My University, 2025)
"This article investigates the role of the apostle Peter in early Christianity as it is presented in Luke-Acts. To this end we offer a narrative analysis of Luke-Acts with a special focus on social interaction. We make use of social network analysis (SNA), a methodology which is briefly explained at the outset. The question of Peter’s role often focuses on the interpretation of specific passages such as Matthew 16:17-19. We will show that paying attention to Peter’s social network with the help of SNA helps us to analyse and indeed reconsider Peter’s role in the early Christian network. We conclude that he was not merely a leader, a person with absolute authority over decisions. Rather, Luke-Acts shows us Peter as a man who sought relationships with people and with God, and who mediated between different perspectives." (Author's abstract, BIBB-Doku)
Keywords: T 4 Bezugswissenschaften; 370; 600; Theologie; Informatik; Soziales Netzwerk; Netzwerkanalyse